Comparisonoftheanteroiferiorarch’sshapewithmandibularselection individualized method of Interlandi on models with normal occlusion - Carhuamaca León, Gregorio Javier (2013)
The aim of the study is to find the shape of arch anteroinferior in normal natural occlusions and relate this finding with the Interlandi’s method of selection of the mandibular anterior arch. The sample was 9 study models of the lower arch (5 males and 4 females between 13-17 years) in normooclusion, with mild crowding, no facet of wear, without coronary fracture, no decay or restorations and without some kind of tooth abnormality in shape, size and number. It was the digitizing of models (with points of reference on cusp of canines, interincisor point and canine distal face) with a graph paper (for the calibration software Corel Draw x 5), with same conditions (brightness, contrast, extension 100) and saved in jpg format. Once calibrated the model image, aligned the cusps of the canines in the horizontal plane. First technique with the formation of the segment arch individualized for each model, formed from three unaligned points (2 points: cusps of canines and 1 point: interincisivo point); Measured the radius, angle, intercanin distance, and height of the arc segment. In this technique, Interlandi primer arc length, was respected and was drawn from the distal face of canines to the origin of the Interlandi arc segment, the total intercanin angle on the template of interlandi and measured total intercanin angle. The data were processed with SPSS 15, evaluating a bivariate analysis (Pearson correlation) for each variable (average, standard deviation, minimum, maximum), between variables in the first technique and comparing the two techniques in related samples (Student’s t). The results obtained for the radius of the previous arc segment has an average of 20, 73mm ± 3.76, compared to the radius of the segment in Interlandi with 20, 66mm ± 3.67, the angle of the anterior arch segment averages 87,48 ° ± 11.54, compared to the angle of the segment in Interlandi with 87,68 ° ± 11.27, distance intercanin in the anterior arch segment has an average of 28, 05mm ± 1.75compared to the intercanin away from the segment in Interlandi 28, 04mm ± 1.78, the height of the anterior arch segment has an average of 5, 61mm ± 0.64, compared to the height of the segment in Interlandi 5, 62mm ± 0.62. The correlation between the variables within the anterior arch segment, found that there is a strong correlation between radius and angle, radius and intercanin distance, radius and height, the same angle and intercanin distance, angle and height, but there is a correlation between the intercanin distance and height. Comparing both methods shows that there is a statistically significant difference for the radius, the angle, the intercanin distance and height of segment of anterior arch with the previous arcs of Interlandi, that there would be no difference any use interlandi diagrams for the selection of the anterio-lower arch. Counter there is difference in the angle of the arc, was the difference that exists between the angle of the segment distal to canines within Interlandi with an average of 110,11 ° ±14,05 mean, and Interlandi’s angle which proposes in its diagram of 120 °, this being statistically significant between the two measures.